Construção de dispositivo com software embarcado de avaliação do reflexo pupilar humano para apoio a diagnóstico oftalmológico - Delfino, Higor Pereira (2021)
The realization of diagnosis through precise metrics, in a fast, safe, efficient way, with non-evasive means and at a low cost, brings great advantages for the medical field. Meeting this need are studies in the field of the human pupillary reflex that demonstrate that the eyes are more than an organ of the sensory system and can provide accurate and reliable biosignals to aid in diagnosis. This work aims to build an automated pupillometry equipment in order to help identify pathologies or disorders, using computer vision techniques. In this sense, this work proposed a pupilometer that can be used in people, capable of stimulating the pupil at various wavelengths, providing a friendly interface and pre-assessing the exam. This work proposes to build a low-cost, easy-to-operate and minimally viable equipment to be used in an ophthalmological office. The equipment built in this work presents adequate quality, automation and configuration flexibility with a great potential of use for several studies in the field of automated pupillometry. Regarding the induction of pupillary reactivity, the equipment is capable of working with flexible and dynamic configurations, and it can be adjusted to the intensity of stimuli and worked with strobe light.